Innovation Business of Unique Wall Clock as an Effort for Utilizing Cardboard Waste - Serevina, Vina; Khoiriyyah Ana Mulyaningrum; Amelia, Dea (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
One of the innovations that can be developed to ‎manage cardboard waste into objects of economic value is to make handicrafts in ‎the form of wall clocks made from cardboard waste. The purpose of this research is to reduce cardboard waste innovatively so that it has a high selling value. In this activity, the method used is a situation survey and ‎the process of making unique wall clocks from collecting cardboard waste to the ‎formation of the final product. This product produces quite promising profits. The sales observation process is carried out for ‎two periods with a cycle per year, sales results are observed based on the cash ‎flow statement, balance sheet, and income statement. Observations show that ‎sales generate increased profits from year to year. This product has a high enough business ‎feasibility to increase people’s income. In addition, this product is expected to be ‎able to benefit the environment and society so that environmental pollution can ‎be reduced. However, there is a threat caused by the development of time other ‎innovations from the same raw materials emerge and the trend of wall clocks that ‎are increasingly developing every time can also slow down the development of ‎this business.